Innovation Of Use Of The Electronic Service Manufacturing Application (Nadine) In The Regional Office Of The Directorate General Of Treasure Of South Sulawesi Province - Muthmainnah, Nurjayanti; Nur, Andi Cudai; Yamin, Muhammad Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine the Innovation in the use of the Electronic Official Manuscript Application (NADINE) at the Regional Office of the Directorate General of Treasury of South Sulawesi Province. This study is qualitative, therefore to achieve the objectives of the study, data collection techniques are used, namely observation, interviews and documentation. This study uses four indicators, namely Having Uniqueness, Having Characteristics or Elements of Renewal, Having a Planned Program, and Having a Purpose. The results of this study indicate that the Innovation in the use of the Electronic Official Manuscript Application (NADINE) at the Regional Office of the Directorate General of Treasury of South Sulawesi Province can be said to be "optimal" based on the indicators of Miles B, Matthew's theory (1973), namely: 1) Having Uniqueness, lies in the automatic notification feature that informs users when a letter or order comes in, then there is an electronic signature feature that can be accessed anytime and anywhere, and there is a real-time document status tracking feature that makes it easier to monitor document flow. 2) Having characteristics or elements of renewal, this Innovation replaces the paper-based manual system with a more efficient digital system. Then there is a standard template feature in document creation to ensure format consistency and minimize errors. With features such as data encryption and user authentication, documents are protected from unauthorized access. 3) Having a Planned Program, the NADINE Application was designed and implemented to overcome obstacles in the management of correspondence that arose during the COVID-19 pandemic. This innovation involves a program that includes needs analysis, application development, intensive training, system trials, socialization, and technical assistance. With structured training, and continuous evaluation, NADINE has been successfully implemented to support more efficient management of official documents in various units. 4) Having a Purpose, the NADINE Application was created with the aim of improving the official document management system, which was previously still done manually and was often time-consuming and prone to errors. Through the implementation of this application, the process of compiling, archiving, and distributing official documents becomes faster, well-organized, and efficient.